Dependence of the Absorption Coefficient of Cosmic Rayson the Thickness of the Air Layer of the Atmosphere - Taroyan, A. S.; Kokanyan, E. P.; Taroyan, Y. A.; Maмyan, А. М.
According to the results of the experiment, the value of the total absorption coefficient of the soft-hard component of cosmic rays decreases with an increase in the length of the layer in atmospheric air, u. gradual increase in density. At the same time, its numerical value decreases by about five times, that is, m-1 up to value m-1, with an increase in the length of the air layer from 25 km to 156.7 km This absorption phenomenon is due to the high absorption coefficient of the soft component, as a result of which their relative amount decreases and the amount of the hard component decreases slightly, since they have a lower absorption coefficient.
Keywords: Physics